STUDENT ENGAGEMENT IN LEARNING IN RUSSIAN UNIVERSITIES - Nataliya G. Maloshonok (Высшее образование в России)
The article presents an attempt of studying peculiarities of the learning process in Russian universities by using concept of student engagement and methodology of measuring it. The data was gathered in three Russian universities. The factor analysis was conducted in order to identify components of student engagement that can describe behavior of students and their attitudes to learning in each investigated university. Results from three Russian universities illustrate that student engagement has significant correlation with academic results and other student characteristics.